Electrochemical Behavior of Manganese Oxide Ores Using Coke Wastewater in Sulfuric Acid Solution. Issue 3 (24th January 2019) - Kang, Jinxing; Feng, Yali; Li, Haoran; Du, Zhuwei; Deng, Xiangyi; Wang, Hongjun
Abstract : The coke wastewater reductive leaching of pyrolusite ore in sulfuric acid solution was studied. This study was performed in two stages. First, the influence of tractable and refractory pollutants of coke wastewater on manganese leaching was determined. It was shown that the leaching efficiency of manganese is very sensitive to the decomposition of intractable pollutants. With the decrease of 1.85 g/L CODcr value of those contaminants, the extraction ratio of manganese increased more than 16% and exceeded 97.3%. Second, the corrosion behavior of pyrolusite ore in simulative wastewater solution was investigated using cyclic voltammograms, polarization curves, and Mott–Schottky curves. The reduction of manganese oxide ore by recalcitrant organic compounds involves two courses—the inducing conversion of manganese oxide to MnO·OH intermediate with hydrogen and free electron, which is from the oxidation of easily oxidized substances and the oxidation of persistent organic matter by this derivative. As a consequence, the latter process leads to the increment in manganese extraction efficiency. Coke wastewater is a promising reducing agent for MnO2 . Likewise, it could be clarified and recycling. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13039, 2019